2019
DOI: 10.1002/jso.25662
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of race and pathology for neuroendocrine tumors: Epidemiology, natural history, or racial disparity?

Abstract: Background and Objectives Although minority race has been associated with worse cancer outcomes, the interaction of race with pathologic variables and outcomes of patients with gastroenteropancreatic neuroendocrine tumors (GEP‐NETs) is not known. Methods Patients from the US Neuroendocrine Study Group (2000‐2016) undergoing curative‐intent resection of GEP‐NETs were included. Given few patients of other races, only Black and White patients were analyzed. Results A total of 1143 patients were included. Median a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, the accuracy and e ciency of the AJCC tumor staging system for patients with PNETs remain doubtful [8]. In recent years, several studies have demonstrated that additional risk factors, including age, sex, race, primary tumor site, and gene mutations, should be included in a novel prognostic indicator system for PNET patients [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy and e ciency of the AJCC tumor staging system for patients with PNETs remain doubtful [8]. In recent years, several studies have demonstrated that additional risk factors, including age, sex, race, primary tumor site, and gene mutations, should be included in a novel prognostic indicator system for PNET patients [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies looking at racial disparities in PNETs found that Black patients had more advanced disease on presentation, a higher rate of emergent surgery, and worse OS. 11,12 However, these prior studies had limited ability to investigate socioeconomic influences. Within this study, we evaluated several socioeconomic factors that are known to impact oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…6,11 Another study analyzing patient data in the US Neuroendocrine Study Group database found that Black patients were significantly more likely to require emergent surgery or have lymph node metastases but had a better 5-year disease-free survival (DFS). 12 These findings point to an underlying racial disparity, but it is uncertain whether these differences are due to disease biology or socioeconomic circumstances. The intersection of socioeconomic factors and neuroendocrine tumor outcomes has been studied in multiple large data sets, predominantly comparing urban with rural patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They compared the non-Hispanic White and non-Hispanic Black patients only and did not include the Hispanic patient population. It showed better disease-free survival in non-Hispanic Black patients despite having a higher lymph node involvement [ 20 ]. Another study from Shen et al, used SEER and SEER-Medicare databases to describe racial differences in the incidence and survival of patients with all distant stage neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%